Cómo aprenden los profesores. Un estudio empírico basado en entrevistas - Manuel Pintor García; Carmen Vizcarro Guarch (Universidad Complutense de Madrid, 2006)
The main aim of this study is to describe the different conceptions that teachers hold about their own learning, and also their relationship to their teaching practice as well as their epistemological beliefs, cognitive and metacognitive strategies and values. The implications of these results for teachers' knowledge acquisition and effective training will be commented, in order to highlight some scientific criteria for these interventions. The socioconstructive character of intelligence and learning is emphasised.